2019
DOI: 10.3390/microorganisms7110507
|View full text |Cite
|
Sign up to set email alerts
|

Defective RNA of a Novel Mycovirus with High Transmissibility Detrimental to Biocontrol Properties of Trichoderma spp.

Abstract: Trichoderma species are a group of fungi which is widely distributed in major terrestrial ecosystems; they are also commonly used as biocontrol agents for many plant diseases. A virus, namely Trichoderma harzianum hypovirus 1 (ThHV1), was identified in T. harzianum isolate T-70, and also infected isolate T-70D, together with its defective RNA (ThHV1-S). The ThHV1 genome possessed two Open Reading Frames (ORFs), namely ORF1 and ORF2. The start codon of ORF2 overlapped with the stop codon of ORF1 in a 43 nt long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Furthermore, mycoviruses can participate in some complex mutualistic symbiosis, enhancing the survival of host fungi and plants under extreme conditions [ 24 ]. In addition, mycoviruses may also be involved in the interaction between biocontrol agents and target phytopathogenic fungi [ 25 ]. Although mycoviruses having biological effects are frequently observed and widely investigated, most mycoviral infections are asymptomatic or cryptic, and this may be related to their lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mycoviruses can participate in some complex mutualistic symbiosis, enhancing the survival of host fungi and plants under extreme conditions [ 24 ]. In addition, mycoviruses may also be involved in the interaction between biocontrol agents and target phytopathogenic fungi [ 25 ]. Although mycoviruses having biological effects are frequently observed and widely investigated, most mycoviral infections are asymptomatic or cryptic, and this may be related to their lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…The inducible genome deletions of MyRV1 dsRNA S4 and S10 are related to changes in vertical transmission efficiency and host colony morphology, but not to viral replication (Sun and Suzuki, 2008;Eusebio-Cope et al, 2010;Kanematsu et al, 2014). Several other findings of RNA genome deletions in the hypoviruses also demonstrated their encoded in-frame fusion proteins affecting host growth negatively (Hillman et al, 2000;Xie et al, 2011;You et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…It effectively controlled tomato gray mold disease (caused by B. cinerea ) and watermelon fusarium wilt (caused by Fusarium oxysporum ) and exhibited plant-growth-promoting ability in tomato and watermelon. In our previous study, we reported a mycovirus from T. harzianum (ThHV1) and its defective RNA (ThHV1-S), and demonstrated that ThHV1-S decreased mycoparasitism and increased the antifungal activity of the culture filtrate (CF) of the host [ 19 ]. A derivative strain 51-13 was obtained by transmission of ThHV-1 and ThHV1-S into the wild-type strain of T. koningiopsis T-51.…”
Section: Introductionmentioning
confidence: 99%
“…A derivative strain 51-13 was obtained by transmission of ThHV-1 and ThHV1-S into the wild-type strain of T. koningiopsis T-51. The derivative strain showed increased antifungal activity against B. cinerea [ 19 ]. In this study, the antifungal activity of CF and VOCs produced by strain 51-13 were evaluated against several pathogenic fungi of plants and the mechanism underlying the effect of ThHV1-S on the host’s antifungal activity was explored.…”
Section: Introductionmentioning
confidence: 99%